Application Analysis of the Language Model - Cai Bochao (ITM Web of Conferences)
Language models(LM) like Claude3, ChatGPT and Llamas have prominent development recent years. However, with the rapid development of theses technology, how to better utilize them and avoid potential risks become an important research topic. Therefore, this paper aims to investigate how these LMs can be better utilized to serve humans and avoid potential risks. This paper mainly analyzes the use of LM in four fields, namely finance, healthcare, entertainment, and customer service to illustrate the usefulness of LMs. It is an emerging technology with considerable potential in various fields to help humans do their jobs better and faster. But at the same time, they may have problems about privacy, decision affectivity, ethics, and unemployment. This essay will hopefully provide a suggestion for the use and specification of LMs that will come later. These tools need to be used correctly, with reasonable avoidance of the risks it poses, to more fully utilize the strengths of LMs.